Pengaruh Non-Performing Financing dan Biaya Operasional Pendapatan Operasional terhadap Return on Assets di BMT Dana Ukhuwah Cabang Cicalengka - Nur'aeni Nur'aeni; Cyntia Dewi; Vemy Suci Asih (Journal of Applied Islamic Economics and Finance, 2021)
The purpose of this study is to explore the factors that affect the profitability of Baitul Maal wat Tamwil (BMT) Dana Ukhuwah Branch Cicalengka. The type of research used is associative quantitative research. In this study, it was obtained from the financial statements of BMT Dana Ukhuwah Period 2016-2020 in the form of Non-Performing Financing (NPF) data, Operational Costs of Operating Income (BOPO), and Return on Assets (ROA). The results showed that NPF had no significant effect on ROA, while BOPO had a significant effect on ROA. NPF and BOPO simultaneously have a significant effect on ROA.